Die Entscheidungen in die politische Arena zurückzuholen: Replik zu Henrik Lebuhn, Sozialräumliche Konflikte in der unternehmerischen Stadt. Eine Berliner Fallstudie, PROKLA 149 - Lederer, Klaus (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2008)
The text is dealing with the article (PROKlA 4/2007) of Henrik Lebuhn on urban entrepreneurial policies based on the example of Berlin. The policy of the town of Berlin is a complex and contradictory process which includes more and other things than being a NPM model town. Lebuhn’s analysis of the conflicts and the lines of debate is strongly reduced, because he doesn’t take into consideration at all the entire development of Berlin since 1990. Contrary to that the autor argues that especially strategic defects of the Berlin left have led to the weakness of alternative political approaches. Instead of eluding the question of an appropriate handling of public resources the left should pick it up head-on and bring it back into the political arena of the town.